Factors contributing building safety and health performance of low cost housing in Malaysia - Ramli, A.; Akasah, Z. A.; Masirin, M. I. M. (2013)
The implementation of safety and health measures on building should be addressed during their life cycles to improve the occupants’ quality of life. However, information concerning the health and safety performance of buildings is not always readily available. This paper aims to determine and identify the factors contributing to safety and health performance of low cost housing in Malaysia. The research first identified the critical factors through a literature review of current safety and health practices from journals, thesis and articles books in order to interpret the factors from a global perspective. A total of fifty questionnaires were then distributed to relevant respondents such as academician, architects, engineers, building surveyors and property managers. In total, 33 completed questionnaires formed a database for descriptive and ranking analysis. The findings of the study revealed that the reliability of the instruments were greater than 0.80. A preliminary finding concluded three factors that the most dominant building design factors contributing to safety and health performance of low cost housing in Malaysia were structural and finishes integrity, amenities and fire services installation. Meanwhile, it was found that three of the most building management factors were documentation and evaluation, building services and structural and finishes integrity. Collectively, results provide evidence that the instruments are reliable in the Malaysian context. However, a bigger sample would be needed to represent the larger population of construction practitioners in Malaysia.